CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O
CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 + S 0 + N +2 O+H 2 O
CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 + S 0 + N +2 O+H 2 O N e → N +2
CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 + S 0 + N +2 O+H 2 O N e → N +2 S -2 – 2e → S 0
CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 + S 0 + N +2 O+H 2 O N e → N +2 S -2 – 2e → S
CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 + S 0 + N +2 O+H 2 O N e → N +2 S -2 – 2e → S
CuS+HNO 3 →Cu(NO 3 ) 2 + S + NO+H 2 O CuS -2 +HN +5 O 3 →Cu(NO 3 ) 2 +3S 0 +2N +2 O+H 2 O N e → N +2 S -2 – 1e → S
CuS + HNO 3 →Cu(NO 3 ) 2 + 3S +2NO + H 2 O 3CuS + HNO 3 → Cu(NO 3 ) 2 + 3S+ NO + H 2 O 3CuS + HNO 3 → 3Cu(NO 3 ) 2 + 3S + 2NO + H 2 O
3CuS +8HNO 3 → 3Cu(NO 3 ) 2 +3S +2N O+H 2 O 3CuS + 8HNO 3 → 3Cu(NO 3 ) 2 + 3S + 2NO + 4H 2 O